# HELPPP

Solve:

3x(x+4)+3(x+4)=0

If you need further help, feel free to contact me for tuition services
Kasim A.
13 April 2017
First, expand the bracketsSo 3x^2+12x + 3x+12 =0Then simplify it all out - ax^2+bx+c=0 is the format you want the question in to solve3x^2 + 15x +12 =0This is the same as 3(x^2+5x+4)=0Now you need to find 2 numbers to multiply to make 4 (c in the equation) that also add to make 5 - 1 and 4.Therefore x=-1 and x=-4Check it in the equation and see if it equals 0, if it does it's right
Kasim A.
13 April 2017
expand the brackets3x^2 + 12x + 3x + 12 = 0Gather like terms3x^2 + 15x + 12=0simplify by dividing the whole equation by 3x^2 + 5x + 4 = 0Factorise (two numbers that added give you 5 and multiplied give you 4)(x+1)(x+4) = 0Thus, the two solutions are x=-1 and x=-4
manfred.olbrich
17 April 2017
given the equation, we can say that we have (x+4) in common.So, we take that out, (x+4), we will have another bracket, (3x+3).We can say that (x+4)(3x+3)=0now we can equate, we can say either (x+4)=0 or (3x+3)=0                                                                                                x=0 -4  or 3x=0-3                                                                                                  x= -4 or x=-3/3                                                                                                      x=-4   or x=-1
shahnaaz1309
21 April 2017
Browndaisha !simply remember in math there is rule of DMAS.  it says 1. Division,2 Multlipication,3.Addition and 4.Subtraction. in any equation follow these steps.you will get result.
mijaz
27 April 2017
3( x+4)(x+1)=0X= -4,  -1
shabanam1982
04 May 2017
3( x+4)(x+1)=0X= -4,  -1
shabanam1982
04 May 2017
Firstly take the bracket of (x+4), if x+4=0 then x must be equal to -4.The other numbers make another bracket of (3x+3). If 3x+3=0, then 3x=-3 and so x is equal to -1
libbydale1
04 May 2017
3x(x+4) = 3x^2 +12x3(x+4) = 3x + 12So: 3x(x+4) + 3(x+4) = 3x^2 +12x + 3x + 12  ----> just expanded the brackets Therefore: 3x^2 +12x + 3x + 12  = 0Simplify it to: 3x^2 + 15x + 12 = 0Factorise to get: (3x + 3) (x+4) = 0Therefore: (3x + 3) = 0 or (x+4) = 0If: 3x + 3 = 0 --> 3x = -3 so x= -3/3 = -1If: x+4 = 0 ---> x = -4x = -1 or -4Hope that helped!
gsethunath
06 May 2017
3x(x+4)+3(x+4)=0(3x+3)(x+4)=03(x+1)(x+4)=0x+1=0 and x+4=0x=-1 or  x=-4
sudarsan
14 May 2017
Let's solve your equation step-by-step.3x(x+4)+3(x+4)=0Step 1: Simplify both sides of the equation3x2+15x+12=0Step 2: Factor left side of equation.3(x+1)(x+4)=0Step 3: Set factors equal to 0.x+1=0 or x+4=0ans:x=−1 or x=−4
amitesh
09 June 2017